Determining the effect of anthropogenic loading on the environmental state of a surface source of water supply - Ponomarenko, Roman; Plyatsuk, Leonid; Hurets, Larysa; Polkovnychenko, Dmytro; Grigorenko, Natalia; Sherstiuk, Mykola; Miakaiev, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2020)
Based on an analysis of forecasting models of the state of surface objects, this paper has proven that it is advisable, when forming a system of operational prediction and evaluation of anthropogenic loads, to apply simpler models that make it possible to promptly conduct calculations. As an approach to the operative forecasting of anthropogenic loading, the application of an approximately necessary level of the reduction of harmful influence on the site of a surface water object in terms of pollutants received has been suggested. Based on a retrospective analysis of data, the mathematical modeling of the indicators of the Dnipro river ecological condition has been performed. It has been determined that the dependence of an increase in the pollutant concentrations on an increase in its mass, within the sections of a watercourse bounded by existing stationary sites, is described by a linear dependence. An analysis of the derived dependences has made it possible to establish that regardless of the type of pollutant, they have IV characteristic points that allow the rapid prediction of an increase in the mass flow rate of the examined contaminating substance and a change in its concentration. It has been established that at equal values of increasing concentrations for non-conservative substances, the increase in the mass flow rate would be less than that under the conditions of "clean dilution". In other words, at an actual water object, increasing the Sp concentration amplifies the natural processes of self-purification. The adequacy of the proposed approach has been tested at an actual surface water object, which has made it possible to establish the linear dependences for a change in the content of sulfates: ∆Csulfate=0.022∙∆msulfate–0.001 and chlorides: ∆Cchloride=0.0143∙∆mchloride–0.033. In its turn, the dependence of sulfate content on chloride content is as follows: ∆Csulfate=1.559∙∆mchloride+2.286. It has been found that for a section of the watercourse in the Dnipro river the linear dependence for phosphates takes the following form: ∆Cphosphate=0.019∙∆mphosphate–0.020; for sulfates: ∆Csulfate=0.022∙∆msulfate–0.001; for chlorides: ∆Cchloride=0,0143∙∆mchloride–0,033. The dependence of phosphate content on sulfate content takes the following form: ∆Cphosphate=0,066∙∆Cchloride+0,422∆Csulfate–0,017. These equations make it possible in the first approximation to calculate an increase in the concentration of a single pollutant under the condition that the gain in the concentration of another one is known, which reduces data volumes and improves the efficiency of forecast calculations.